Comprehensive Physiology 2015
DOI: 10.1002/cphy.c140053
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Fibroblast Physiology and Pathology

Abstract: Cardiac function is mediated by interactions between the cellular constituents of the heart, as well as the extracellular matrix. The major cell types of the heart include cardiac fibroblasts, myocytes, endothelial cells, and vascular smooth muscle cells. In addition, there are also resident stem cells and transient cell types, such as immune cells. Interactions in the heart include chemical, mechanical, and electrical signals, which vary depending on the developmental stage, disease state, and specific cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 289 publications
0
42
0
1
Order By: Relevance
“…Cardiac fibroblasts are one of the most-prevalent, nonmyocyte cell populations in the heart, accounting for between one-fifth and two-thirds of cardiac cells, depending on the species (16)(17)(18). Although traditionally viewed solely in relation to extracellular matrix remodeling, cardiac fibroblasts are now acknowledged as being important nodal regulators of multiple aspects of cardiac function under both physiologic and pathophysiologic conditions (19)(20)(21). Importantly, recent studies have revealed that fibroblasts have a critical role in inducing cardiomyocyte hypertrophy in vivo through paracrine secretion of growth factors and other signaling molecules (22,23).…”
mentioning
confidence: 99%
“…Cardiac fibroblasts are one of the most-prevalent, nonmyocyte cell populations in the heart, accounting for between one-fifth and two-thirds of cardiac cells, depending on the species (16)(17)(18). Although traditionally viewed solely in relation to extracellular matrix remodeling, cardiac fibroblasts are now acknowledged as being important nodal regulators of multiple aspects of cardiac function under both physiologic and pathophysiologic conditions (19)(20)(21). Importantly, recent studies have revealed that fibroblasts have a critical role in inducing cardiomyocyte hypertrophy in vivo through paracrine secretion of growth factors and other signaling molecules (22,23).…”
mentioning
confidence: 99%
“…Upon cardiac injury, CF respond to these signals by transforming to smooth muscle actin-expressing “myofibroblasts,” leading to changes in proliferation and migration as well as secretion of ECM proteins to promote wound healing (Figure 2). Myofibroblasts secrete large amounts of ECM proteins including collagens, fibronectin, periostin, MMPs and their inhibitors, TIMPs [110, 111]. Specifically, CF have been shown to secrete MMP-1,-2,-3,-9,-13,-14 and TIMP-1,-2,-3 and -4 after injury or pathologic stimulation [14, 112, 113].…”
Section: Ecm-cell Interactions In the Injured Myocardiummentioning
confidence: 99%
“…Fibroblasts also produce a number of cytokines, peptides, and enzymes including matrix metalloproteinases (MMPs) and their inhibitors, tissue inhibitors of metalloproteinases (TIMPs) that directly affect the ECM turnover and homeostasis. In turn, as a feedback, function of fibroblasts can also be regulated by MMPs and TIMPs [12,13].…”
Section: Cardiac Fibroblastsmentioning
confidence: 99%